A Taxonomy of Supply Chain Collaboration - Simatupang, Togar Mangihut (SBM ITB, 2007)
Supply chain collaboration has emerged as an important cooperative strategy leading to new focus on interorganisational boundaries as the determinants of performance. Although collaboration increasingly receives great attention both from practitioners and academics, relatively little attention has been given to systematically reviewing the research literature that has appeared about supply chain collaboration. The purpose of this paper is to examine previous studies on supply chain collaboration based on a taxonomy. The proposed taxonomy is composed of four different research streams of describing specific subjects of interorganisational settings, namely information sharing, business processes, incentive schemes, and performance systems. The analysis includes the assessment of research ideas and key findings. Results show the great variability of key concepts across the four components of the taxonomy and an increased awareness of complementarity amongst research streams. Several recommendations for future research are also identified in this paper.Â Keywords: supply chain collaboration, literature review, supply chain management, taxonomy